Hajj and Self-Transformation: The Moral Anchoring of Sustained Prosocial Behavior among Indonesian Pilgrims - Putri, Risa Mai; Hasanah, Hasyim (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
This study examines how the Hajj pilgrimage shapes sustained prosocial behavior among Indonesian pilgrims, with a focus on the mechanisms that support post-pilgrimage transformation. While previous studies have documented the spiritual and social impacts of Hajj, less attention has been given to how such changes are maintained in everyday life. This study addresses that gap by analyzing how internal transformation is translated into consistent prosocial behavior. Using a qualitative interpretive design, data were collected from fourteen participants across diverse regions in Indonesia through open-ended narrative responses and focused observations. Participants were selected based on demonstrated post-Hajj behavioral change to capture cases of sustained transformation. Data were analyzed through thematic coding to identify patterns of change and the processes underlying behavioral consistency. The findings show that transformation unfolds through a sequence of character reconstruction, value reorientation, and social role actualization. A key shift occurs in motivational orientation, where prosocial behavior becomes internally driven and integrated into daily routines. The study also identifies a moral anchoring process, in which the Hajj identity functions as a stabilizing reference that supports self-regulation and behavioral consistency over time. These findings suggest that the impact of Hajj extends beyond ritual experience and depends on how its meaning is internalized and sustained in social life. The study contributes to discussions on religious transformation by offering a process-based explanation of how prosocial behavior is maintained. It also highlights the importance of post-Hajj engagement in supporting long-term social outcomes.